Asuhan Keperawatan Pada Ny.S P2a0 Post Partum Spontan Disertai Ketuban Pecah Dini Di Ruang Mawar Rsud Surakarta - Saidah, Hani, Sulastri, S.Kp., M.Kes (2015)
Background: Labor is a complex process in order to save the mother and the baby at every vaginal delivery or spontaneous parturition, indications often occurs like as premature rupture of membranes. If premature rupture occurs at gestational age of 36 weeks and still no sign of labor is carried out labor induction. Purpose: To determaine nursing care in patients with post partum accompanied spontaneous premature rupture of membrances covering assessment, nursing diagnosis, nursing interventions, implementation and evaluation. Result : After the 2 x 24 hour nursing care for the results obtained, understanding about baby care home, understand about the importance of immunization to the baby and less knowledge of the breast in patients resolved. Conclusion : Collaboration betweens teams with the client or family is indispensable for the success of nursing care therapeutic communication can en curge more cooperative clients on the application of the nursing care post partum spontaneous premature rupture of membranes accompanied all nursing problems resolved. Keyword: Post partum spontaneous, Premature rupture of membranes.